OPERATION OF TRANSPORT SYSTEMS IN EMERGENCY CONDITIONS - Кіркін, Олександр; Кіркіна, Тетяна (SWorldJournal, 2022)
The paper considers the operation of transport systems in the conditions of making time-limited and resource-limited decisions to optimize, maintain stability, controllability and survival. The concepts of risk, uncertainty, fuzziness make it possible to